Evaluating the use of web-based games on students' vocabulary retention - Zuraina, Ali; Norsuhaily, Abu Bakar; Ahmad, Waqar; Jumadil, Saputra (Growing Science, Canada, 2022)
Today, the use of technology has made education more enjoyable. Vocabulary retention becomes a challenging task for both teachers and learners. They may learn the vocabulary but may not retain it. Yet, the use of web-based games may assist them in maintaining words known for short and longterm retention. The current study was conducted to identify students' abilities in retaining words learned after they were assigned to play a web-based vocabulary learning game, namely OnVac. Both short and long-term retention were measured after they were required to play the game as a treatment. Also, the study investigated students' perceptions about the system operation of OnVac. The use of quantitative research design, particularly quasi-experimental research and survey showed gains in vocabulary retention among students for short and long-term retention. The study also found that OnVac can support vocabulary learning among students in their learning of the specialized vocabulary. In terms of the system operation, the participants reported that the tool could assist them in learning engineering and technology words as it was convenient to use. The study provided implications to the teaching pedagogy in that teachers need to be wise and analytical in developing the online game to assist learners in learning English specialized vocabulary.